Geriatric Diabetes Care: Prescribing Practices and Drug Utilisation at a Teaching Hospital - Kumar, Rahul; Singh, Harmanpreet; Singh, Arshdeep; Agrawal, Bimal K; Das, Rina; Garg, Dhanesh; Mehta, Dinesh Kumar (Scripta Medica, 2026)
Background/Aim: Diabetes is increasingly recognised as a major health concern worldwide, affecting around 537 million adults and causing approximately 6.7 million deaths annually. In India alone, 74.9 million individuals had diabetes in 2021 and this figure could rise to 124.9 million by 2045. Older adults (aged 60 and above) are particularly affected, with 14.3 % of them living with type 2 diabetes. Managing diabetes among the elderly is complicated, as they often have other health conditions and are on multiple medications, which can lead to issues such as polypharmacy and harmful drug or food interactions. Consequently, it is crucial to examine how diabetes medications are being prescribed for this age group. Methodology: A prospective cross-sectional study was conducted among geriatric patients (≥ 60 years) at a tertiary care teaching Hospital in Mullana, Ambala, Haryana, over six months from December 2024 to May 2025. Study samples were selected through systematic random sampling and each prescription was evaluated to analyse prescribing patterns, polypharmacy and drug interactions. Additionally, patient’s quality of life was assessed.Results: A total of 185 patients participated in the study, including 96 males (51.9 %) and 89 females (48.1 %), with a mean age of 66.58 ± 6.26 years. Metformin was the most commonly prescribed monotherapy, followed by glimepiride, human insulin and dapagliflozin. The most frequent combination therapy was metformin with vildagliptin (17.2 %). Hypertension (22.7 %) was the most prevalent comorbidity. Polypharmacy was observed in 80 % of patients, drug-drug interactions in 84.3 % and food-drug interactions in 29.9 %. The average quality-of-life score was 67.74 ± 13.53 %, with lower scores among those aged over 80.Conclusion: The study highlights prevalent polypharmacy, drug interactions and comorbidities among elderly diabetics, emphasising the need for rational prescribing to enhance treatment efficacy, minimise adverse effects and improve quality of life. Overall, the study underscores the importance of rational prescribing and optimised drug use in elderly diabetic patients to improve outcomes and reduce adverse effects.
Keywords: Diabetes mellitus; Aged; Patients; Polypharmacy; Drug interactions; Quality of life